2022
DOI: 10.22146/jpki.69550
|View full text |Cite
|
Sign up to set email alerts
|

The Readiness for Interprofessional Education Implementation During Covid-19 Pandemic in Indonesia: A Descriptive Study

Abstract: Background: The importance of the interprofessional education (IPE) program has been depicted through various forms of the IPE curriculum. The COVID-19 pandemic has forced a change in the implementation of IPE; this has caused the method of implementing IPE to change online. This study aims to assess the readiness of three different healthcare professions for implementing IPE using the Readiness for Interprofessional Learning Scale (RIPLS).Methods: The RIPLS survey was completed by 108 medical students, 40 pha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…Qualitative data analysis further indicated that IPE increased the awareness of team members' roles, enhanced communication and collaboration, and contributed to better care for COVID-19 patients [32]. In a previous study that evaluated the readiness for IPE conducted online targeting healthcare students in Indonesia, explorations of the perceived competency identity scores for IPE competencies revealed a higher number of positive perceptions [33]. In our study, the post-IPE scores of the online group were significantly higher in all subscales of the RIPLS, suggesting a positive educational effect of online IPE sessions.…”
Section: Discussionmentioning
confidence: 86%
“…Qualitative data analysis further indicated that IPE increased the awareness of team members' roles, enhanced communication and collaboration, and contributed to better care for COVID-19 patients [32]. In a previous study that evaluated the readiness for IPE conducted online targeting healthcare students in Indonesia, explorations of the perceived competency identity scores for IPE competencies revealed a higher number of positive perceptions [33]. In our study, the post-IPE scores of the online group were significantly higher in all subscales of the RIPLS, suggesting a positive educational effect of online IPE sessions.…”
Section: Discussionmentioning
confidence: 86%